A metric-based analysis of structure and content of telephone consultations of final-year medical students in a high-fidelity emergency medicine simulation. Issue 5 (13th September 2012) - Henn, Patrick; Power, David; Smith, Simon D; Power, Theresa; Hynes, Helen; Gaffney, Robert; McAdoo, John D
Abstract : Objectives: In this study we aimed to analyse the structure and content of telephone consultations of final-year medical students in a high-fidelity emergency medicine simulation. The purpose was to identify any areas of deficiency within structure and content in the effective transfer of clinical information via the telephone of final-year medical students. Design: An educational study. Setting: Simulation centre in a medical school. Participants: 113 final-year medical students. Primary and secondary outcomes: The primary outcome was to analyse the structure and content of telephone consultations of final-year medical students in a high-fidelity emergency medicine simulation. The secondary outcome was to identify any areas of deficiency within structure and content in the effective transfer of clinical information via the telephone of final-year medical students. Results: During phone calls to a senior colleague 30% of students did not positively identify themselves, 29% did not identify their role, 32% did not positively identify the recipient of the phone call, 59% failed to positively identify the patient, 49% did not read back the recommendations of their senior colleague and 97% did not write down the recommendations of their senior colleague. Conclusions: We identified a deficiency in our students skills to communicate relevant information via the telephone, particularly failure to repeat back and write down instructions. We suggest that this reflects a paucity of opportunities to practice this skill in context during the undergraduate years. The assumption that this skill will be acquired following qualification constitutes a latent error within the healthcare system. The function of undergraduate medical education is to produce graduates who are fit for purpose at the point of graduation.